Comparison of microbial abundance and diversity in uterine and peritoneal fluid in infertile patients with or without endometriosis - Jue Zhu; Yichen Chen; Huan Chen; Yuhui Sun; Lifeng Yan; Miaohua Zhu; Liang chen; Qiming Wang; Jing Zhang (BMC, 2024)
Abstract Introduction Endometriosis (EM) is a multifactorial disease that affects 10 − 15% of women of reproductive age. Additionally, 30-50% of women with EM suffer from infertility. The mechanism of infertility caused by EM has not yet been consistently explained. In recent years, studies have shown a link between infertility associated with EM and changes in the reproductive tract microbiota. Methods In this study, we involved 26 EM patients (8 cases of stage I-II and 18 cases of stage III-IV) and 31 control subjects who were tubal obstruction-related infertility (TORI). The samples from peritoneal fluid (PF) and uterine fluid (UF) were collected and sequenced by 16 S rRNA amplicon. Results In the comparison of microbial diversity, we found no significant differences in the microbial diversity of PF and UF between patients with stage I-II EM and those with TORI. However, there was a significant difference in microbial diversity among patients with stage III-IV EM compared to the previous two groups. Lactobacillus decreased in PF of EM compared to the control group, while it increased in UF. In PF, the abundance of Pseudomonas, Enterococcus, Dubosiella and Klebsiella was significantly higher in patients with stage III-IV compared to TORI patients. And in UF, the main differences existed between stage I-II EM compared to the other two groups. The abundance of pontibacter, aquabacterium, Rikenellaceae and so on at the genus level was significantly enriched in the EM patients with stage I-II. In the analysis based on KEGG database, EM may affect the receptivity related pathways of the endometrium by influencing changes in the uterine microbiota. Conclusion Our results indicated that as EM progresses, the microorganisms in UF and PF keep changing. These changes in the microbiota, as well as the resulting alternations in gene functional classification, may play an important role in the infertility associated with EM.